# Probability of finding a random mass

Suppose we have a list of distinctive elements: $$X_0=\{x_1,x_2,x_3,\cdots,x_n\}$$ Each element has mass 1. Suppose we take two elements at random and make a new element with appropriate mass. For example we take $x_1$ and $x_n$ and we make a new elements $(x_{n+1})$ of mass two, we put the new element back in the list so, $$X_1=\{x_1,x_2,x_3,\cdots,x_n,x_{n+1}\}$$ Now if we repeat this procedure $t$ times we will have $$X_t=\{x_1,x_2,x_3,\cdots,x_n,x_{n+1},x_{n+2},x_{n+3},\cdots,x_{n+t}\}$$ Surely as the process of taking two elements and making a new one is random the masses also will be distributed randomly. Now I was wondering can anyone use probability theory and compute the mass of particle $x_i$ at a given time?

• Just an observation: If $F_1 = F_2 = 1$ are the first two Fibonaccy numbers and $F_{n + 2} = F_{n + 1} + F_n$, then $2\leq x_{n + t}\leq F_t$ and $x_{n + t}$ can take any integer value from this interval. Commented Apr 13, 2018 at 12:15
• The comment by Antoine is correct if the two summands must be different. In my answer I assumed that they can also be the same (= uniformly random picked from two equal sets). Please clarify this aspect. Commented Apr 25, 2018 at 0:44

One could try to solve the problem recursively. There may be better ideas and there may be a simple expression. This is just a thought.

Define $x_i \hat{=} x_{n+i}$. Denote the expectation of the mass of an element $x_i$ by $\mathbb{E}[x_i]$. Then the mass of $x_i$ is generated by two elements $x_j$ with $0 \leq j \leq i-1$. Denote the event that $x_{i-1}$ is chosen to calculate the mass of $x_i$ by $A_i$. Then $$\mathbb{E}[x_i] = \mathbb{E}[x_i | A_i] \mathbb{P}(A_i) + \mathbb{E}[x_i | A_i^c] \mathbb{P}(A_i^c)$$ We already know that if $x_{i-1}$ is not used to calculate the new mass then the expectation should stay the same, thus $\mathbb{E}[x_i | A_i^c] = \mathbb{E}[x_{i-1}]$. The probability of $A_i^c$ is also easily computed by $\mathbb{P}(A_i^c) = \frac{n+i-2}{n+i-1}\frac{n+i-3}{n+i-2}$ and $\mathbb{P}(A_i) = 1 -\mathbb{P}(A_i^c)$. $\mathbb{E}[x_i | A_i]$ can be calculated by $$\mathbb{E}[x_i | A_i] = \mathbb{E}(x_{i-1}) + \mathbb{E}(X_{i-2}) = \mathbb{E}(x_{i-1}) + \frac{n + \sum_{j=1}^{i-2}{\mathbb{E}(x_j)}}{n+(i-2)}$$ Putting it together: $$\mathbb{E}[x_i] = \mathbb{E}[x_{i-1}] + \frac{2 \sum_{j=1}^{n+i-2}\mathbb{E}(x_j)}{(n+i-1)(n+i-2)}$$

• what is $A^c$ denotes? Commented Apr 13, 2018 at 14:22
• The complement of $A$ Commented Apr 13, 2018 at 14:39
• Isn't there an i missing in the last term of the first equation? Commented Apr 13, 2018 at 15:02
• Okay I fixed that now. Is the answer somewhat in the range of what you wanted to know? Commented Apr 13, 2018 at 15:15
• also the X should be x in the second equation I think. Well so I have done the procedure as I asked it numerically. I have some masses for 1000 particles over 100,000 iterations. I want to check how I can know the mass of particle x at time t. So everytime one makes a new mass the probability of that mass is related to the probability of the masses before. Commented Apr 13, 2018 at 15:22

If we have two discrete random variables $X_1,\, X_2$, with $P(X_1=m)=p_1(m),\;P(X_2=m)=p_2(m)$, where $0 \le m \in \mathbb Z$, and $p_j(m)$ is the "Probability Mass Function (pmf)" of each of them, and consider the "Probability Generating Function (pgf)" of each, i.e. $$F_{\,j} (z) = \sum\limits_{0\, \le \,k} {p_{\,j} (k)\,z^{\,k} }$$ then the pgf of the sum will be the product of the single pgf's $$F_{\,1 + 2} (z) = F_{\,1} (z)\,F_{\,2} (z) = \sum\limits_{0\, \le \,k} {\left( {\sum\limits_{0\, \le \,l\,\left( { \le \,k} \right)} {p_{\,1} (l)p_{\,2} (k - l)} } \right)\,z^{\,k} }$$

We will have $$\mathop {\lim }\limits_{z\, \to \,1\, - } F_{\,\Sigma \,2} (z) = F_{\,\Sigma \,2} (1^{\, - } ) = 1$$ and, if it exists, $$E\left( {X_{\,1} + X_{\,2} } \right) = \mathop {\lim }\limits_{z\, \to \,1\, - } F_{\,\Sigma \,2} '(z) = F_{\,\,1} '(1^{\, - } )F_{\,\,2} (1^{\, - } ) + F_{\,\,1} (1^{\, - } )F_{\,\,2} '(1^{\, - } ) = E\left( {X_{\,1} } \right) + E\left( {X_{\,2} } \right)$$

So if we have $q$ variables, among which we choose the pair $(i,j)$ to sum uniformly at random, e.g. from an urn, there are two common schemes that we can adopt

a) with replacement, which means that the couples with same elements are included, that we have a prob. $1/q^2$ to choose a specific couple, and that the pgf of the sum of all the possible couples will be $$\bbox[lightyellow] { F_{\,\Sigma \,q} (z) = {1 \over {q^2 }}\sum\limits_{1\, \le \,i,\,j\, \le \,q} {F_{\,i} (z)\,F_{\,j} (z)} } \tag{1.a}$$

b) without replacement, that means that only couples with different elements are included, that the probability to choose a couple is $1/(q^2-q)=1/(q(q-1))$, and that the pgf of the sum of all couples will be \bbox[lightyellow] { \eqalign{ & G_{\,\Sigma \,q} (z) = {1 \over {q\left( {q - 1} \right)}}\sum\limits_{1\, \le \,i \ne \,j\, \le \,q} {G_{\,i} (z)\,G_{\,j} (z)} = \cr & = {2 \over {q\left( {q - 1} \right)}}\sum\limits_{1\, \le \,i\, < \,j\, \le \,q} {G_{\,i} (z)\,G_{\,j} (z)} = \cr & = {1 \over {q\left( {q - 1} \right)}}\left( {\sum\limits_{1\, \le \,i,\,j\, \le \,q} {G_{\,i} (z)\,G_{\,j} (z)} - \sum\limits_{1\, \le \,i\, \le \,q} {G_{\,i} (z)^{\,2} } } \right) \cr} } \tag{1.b}

In our case we are starting with $n$ discrete variables whose pmf is given by
$$\delta (m - 1) = \left[ {1 = m} \right]$$ where $\delta$ denotes the Kronecker's Delta and $[P]$ denotes the Iverson bracket.
The pgf's are identical and equal to $z$.

Then, the first particle generated from the original $n$ will have a spread of values whose pmf \bbox[lightyellow] { \eqalign{ & F_{\,n + 1} (z) = {1 \over {n^2 }}\sum\limits_{1\, \le \,i,\,j\, \le \,n} {F_{\,i} (z)\,F_{\,j} (z)} = \cr & = {1 \over {n^{\,2} }}\sum\limits_{1\, \le \,i\, \le \,n} {F_{\,i} (z)\sum\limits_{1\, \le \,i\, \le \,n} {\,F_{\,j} (z)} } = {1 \over {n^{\,2} }}\left( {n\,F_{\,1} (z)} \right)^{\,2} = \cr & = z^{\,2} \cr} } \tag{2.a} and for case b) \bbox[lightyellow] { \eqalign{ & G_{\,n + 1} (z) = {1 \over {n\left( {n - 1} \right)}}\left( {\sum\limits_{1\, \le \,i,\,j\, \le \,n} {G_{\,i} (z)\,G_{\,j} (z)} - \sum\limits_{1\, \le \,i\, \le \,n} {G_{\,i} (z)^{\,2} } } \right) = \cr & = {1 \over {n\left( {n - 1} \right)}}\left( {n^{\,2} z^{\,2} - n\,z^{\,2} } \right) = z^{\,2} \cr} } \tag{2.b} which is obvious since the sum can only give $2$ in both cases, and proceeding with \bbox[lightyellow] { \eqalign{ & F_{\,n + 2} (z) = {1 \over {\left( {n + 1} \right)^2 }}\sum\limits_{1\, \le \,i,\,j\, \le \,n + 1} {F_{\,i} (z)\,F_{\,j} (z)} = \cr & = {1 \over {\left( {n + 1} \right)^2 }}\sum\limits_{1\, \le \,i\, \le \,n + 1} {F_{\,i} (z)\sum\limits_{1\, \le \,\,j\, \le \,n + 1} {\,F_{\,j} (z)} } = \cr & = {1 \over {\left( {n + 1} \right)^2 }}\left( {n\,z + z^2 } \right)^2 \cr} } \tag{3.a} and \bbox[lightyellow] { \eqalign{ & G_{\,n + 2} (z) = {1 \over {n\left( {n - 1} \right)}}\left( {\sum\limits_{1\, \le \,i,\,j\, \le \,n + 1} {G_{\,i} (z)\,G_{\,j} (z)} - \sum\limits_{1\, \le \,i\, \le \,n + 1} {G_{\,i} (z)^{\,2} } } \right) = \cr & = {1 \over {n\left( {n - 1} \right)}}\left( {\left( {n\,z + z^2 } \right)^2 - \left( {n\,z^{\,2} + z^4 } \right)} \right) = \cr & = {1 \over {n\left( {n - 1} \right)}}\left( {n\left( {n - 1} \right)\,z^2 + 2n\,z^3 } \right) \cr} } \tag{3.b}

After that the recurrence is clear, and for case a), it is $$\bbox[lightyellow] { \begin{array}{l} F_{\,n + \,t + 1} (z) = F_{\,\left[ {n,\,\,t + 1} \right]} (z)\quad \left| {\;0 \le t} \right.\quad = \\ = \sum\limits_{1\, \le \,i,\,j\, \le \,n + t} {\frac{1}{{\left( {n + t} \right)^{\,2} }}F_{\,i} (z)F_{\,j} (z)} = \\ = \frac{1}{{\left( {n + t} \right)^{\,2} }}\left( \begin{array}{l} \sum\limits_{\left\{ {\begin{array}{*{20}c} {\,1\, \le \,i \le \,n} \\ {1\, \le \,j \le \,n} \\ \end{array}} \right.} {F_{\,i} (z)F_{\,j} (z)} + \sum\limits_{\left\{ {\begin{array}{*{20}c} {\,n + 1\, \le \,i \le \,n + t} \\ {\,1\, \le \,j \le \,n} \\ \end{array}} \right.} {F_{\,i} (z)F_{\,j} (z)} + \\ + \sum\limits_{\,\left\{ {\begin{array}{*{20}c} {\,1\, \le \,i \le \,n} \\ {\,n + 1\, \le \,j \le \,n + t} \\ \end{array}} \right.} {F_{\,i} (z)F_{\,j} (z)} + \sum\limits_{\left\{ {\begin{array}{*{20}c} {\,n + 1\, \le \,i \le \,n + t} \\ {\,n + 1\, \le \,j \le \,n + t} \\ \end{array}} \right.} {F_{\,i} (z)F_{\,j} (z)} \\ \end{array} \right) = \\ = \frac{1}{{\left( {n + t} \right)^{\,2} }}\left( {n^{\,2} z^{\,2} + 2n\,z\sum\limits_{\,1\, \le \,k \le \,t} {F_{\,\left[ {n,k} \right]} (z)} + \sum\limits_{\,1\, \le \,k \le \,t} {F_{\,\left[ {n,k} \right]} (z)} \sum\limits_{\,1\, \le \,k \le \,t} {F_{\,\left[ {n,k} \right]} (z)} } \right) = \\ = \frac{1}{{\left( {n + t} \right)^{\,2} }}\left( {n^{\,2} z^{\,2} + 2n\,z\sum\limits_{\,1\, \le \,k \le \,t} {F_{\,\left[ {n,k} \right]} (z)} + \left( {\sum\limits_{\,1\, \le \,k \le \,t} {F_{\,\left[ {n,k} \right]} (z)} } \right)^{\,2} } \right) = \\ = \frac{1}{{\left( {n + t} \right)^{\,2} }}\left( {n\,z + \sum\limits_{\,1\, \le \,k \le \,t} {F_{\,\left[ {n,k} \right]} (z)} } \right)^{\,2} = \\ \;\left| {\;1 \le t} \right. \\ = \frac{1}{{\left( {n + t} \right)^{\,2} }}\left( {n\,z + \sum\limits_{\,1\, \le \,k \le \,t - 1} {F_{\,\left[ {n,\,k} \right]} (z)} + F_{\,\left[ {n,\,t} \right]} (z)} \right)^{\,2} = \\ = \frac{1}{{\left( {n + t} \right)^{\,2} }}\left( {\frac{{\left( {n + t - 1} \right)^{\,2} }} {{\left( {n + t - 1} \right)^{\,2} }}\left( {n\,z + \sum\limits_{\,1\, \le \,k \le \,t - 1} {F_{\,\left[ {n,\,k} \right]} (z)} } \right)^{\,2} + F_{\,\left[ {n,\,t} \right]} (z)^{\,2} + 2F_{\,\left[ {n,\,t} \right]} (z)\frac{{\left( {n + t - 1} \right)}} {{\left( {n + t - 1} \right)}}\left( {n\,z + \sum\limits_{\,1\, \le \,k \le \,t - 1} {F_{\,\left[ {n,k} \right]} (z)} } \right)} \right) = \\ = \frac{{F_{\,\left[ {n,\,t} \right]} (z)}}{{\left( {n + t} \right)^{\,2} }}\left( {\left( {n + t - 1} \right)^{\,2} + F_{\,\left[ {n,\,t} \right]} (z) + 2\left( {n + t - 1} \right)\sqrt {F_{\,\left[ {n,\,t} \right]} (z)} } \right) = \\ = \frac{{F_{\,\left[ {n,\,t} \right]} (z)}}{{\left( {n + t} \right)^{\,2} }}\left( {\left( {n + t - 1} \right) + \sqrt {F_{\,\left[ {n,\,t} \right]} (z)} } \right)^{\,2} \\ \end{array} } \tag{4}$$ i.e., the particle generated at step $t$ will have a spread of values, whose pmf corresponds to the pgf $$\bbox[lightyellow] { F_{\,n + \,t} (z) = F_{\,\left[ {n,\,\,t} \right]} (z) = \left\{ {\begin{array}{*{20}c} z & {\left| {\;0 = t} \right.} \\ {z^{\,2} } & {\left| {\;1 = t} \right.} \\ \begin{array}{l} \frac{1}{{\left( {n + t - 1} \right)^{\,2} }}\left( {n\,z + \sum\limits_{\,1\, \le \,k \le \,t - 1} {F_{\,\left[ {n,k} \right]} (z)} } \right)^{\,2} = \\ = \frac{{F_{\,\left[ {n,\;t - 1} \right]} (z)}}{{\left( {n + t - 1} \right)^{\,2} }}\left( {\left( {n + t - 2} \right) + \sqrt {F_{\,\left[ {n,\;t - 1} \right]} (z)} } \right)^{\,2} \\ \end{array} & {\left| {\;2 \le t} \right.} \\ \end{array}} \right. } \tag{5.a}$$ where the particular notation on the index of $F$ is just to help and separate the original masses from those generated therefrom.

Similarly, it is not difficult to arrive to get $$\bbox[lightyellow] { {G_{\,\left[ {n,\,\,t} \right]} (z) =} = \left\{ {\begin{array}{*{20}c} z & {\left| {\;0 = t} \right.} \\ {z^{\,2} } & {\left| {\;1 = t} \right.} \\ \begin{array}{l} \frac{1}{{\left( {n + t - 1} \right)\left( {n + t - 2} \right)}}\left( {\left( {n\,z + \sum\limits_{\,1\, \le \,k \le \,\,t - 1} {G_{\,\left[ {n,\;k} \right]} (z)} } \right)^{\,2} - nz^{\,2} - \sum\limits_{\,1\, \le \,k \le \,\,t - 1} {G_{\,\left[ {n,\,\,k} \right]} (z)^{\,2} } } \right) = \\ = \frac{{2\,G_{\,\left[ {n,\;t - 1} \right]} (z)}}{{\left( {n + t - 1} \right)\left( {n + t - 2} \right)}}\left( {\left( \begin{array}{c} n + t - 2 \\ 2 \\ \end{array} \right) + n\,z + \sum\limits_{\,1\, \le \,k \le \,\,t - 2} {G_{\,\left[ {n,\;k} \right]} (z)} } \right) \\ \end{array} & {\left| {\;2 \le t} \right.} \\ \end{array}} \right. } \tag{5.b}$$

Taking for example some first few values, we get \eqalign{ & F_{[2,\, 2]} = 1/9 z^2 (z + 2)^2 \cr & F_{[2,\, 3]} = 1/1296 z^2 (z + 2)^2 (2 z + z^2 + 9)^2 \cr & = 1/1296 (z^8 + 8*z^7 + 42*z^6 + 140*z^5 + 313*z^4 + 468*z^3 + 324*z^2) \cr & F_{[2,\, 4]} = 1/41990400 z^2 (z + 2)^2 (18 z + 13 z^2 + 4 z^3 + z^4 + 144)^2 (2 z + z^2 + 9)^2 \cr }

\eqalign{ & F_{[3,\, 2]} = 1/16 z^2 (z + 3)^2 \cr & F_{[3,\, 3]} = z^2 (z + 3)^2 (3 z + z^2 + 16)^2 \cr & = 1/6400 (z^8 + 12*z^7 + 86*z^6 + 396*z^5 + 1201*z^4 + 2400*z^3 + 2304*z^2) \cr & F_{[3,\, 4]} = 1/1474560000 z^2 (z + 3)^2 (3 z + z^2 + 16)^2 (48 z + 25 z^2 + 6 z^3 + z^4 + 400)^2 \cr } and the following sketch of the pmf for $n=2$ and a few values of $t$. Note that the $x$ is scaled by $1/2^t$.

Finally, taking $F'(1)$ and $G'(1)$ we get for the expected value of particle $t$ the same recurrence and solution as follows $$\bbox[lightyellow] { E_{\,\left[ {n,\,\,t} \right]} = \left\{ {\begin{array}{*{20}c} 1 & {\left| {\;0 = t} \right.} \\ 2 & {\left| {\;1 = t} \right.} \\ {\frac{2}{{\left( {n + t - 1} \right)}}\left( {n + \sum\limits_{\,1\, \le \,k \le \,\,t - 1} {E_{\,\left[ {n,\,\,k} \right]} } } \right)} & {\left| {\;2 \le t} \right.} \\ \end{array}} \right.\quad = \quad \left[ {0 = t} \right] + 2\left[ {1 \le t} \right]\left( {1 + \frac{{t - 1}}{{n + 1}}} \right) } \tag{6}$$ Upon some thought, the recursion comes out to be obvious. I was not expecting instead that the average value was increasing linearly with $t$

• Thanks for this answer. Is OGF just technically the PGF (probability generating function)? Also as far as I am aware in order to obtain the expected value one should calculate $F'(z=1)$ is that correct? Also what is the MDF? Commented Apr 23, 2018 at 10:03
• @G Cab Can you please clarify how to you calculate the second term of (4) exactly? Commented Apr 24, 2018 at 10:32
• also n is the initial number of elements and q is the n+t in your notation, am I correct? Commented Apr 24, 2018 at 10:33
• @William I have amended my answer to make it clear in the denominations and in the derivation of eq. (4). Respect to the previous version, let's clarify that, the power series related to a general sequence $F(z)=\sum\limits_{0\, \le \,k} {a_k\,z^{\,k} }$ is called "Ordinary Generating Function (ogf)" . A special case is when the sequence represents the values of the "Probability Mass Function (pmf)" of a discrete random variable, which are all non-negative and sum to $1$, then must be $F(1^-)=1$. This special case is called "Probability Generating Function (pgf)". Commented Apr 24, 2018 at 21:51
• @William: a) True that $F'(1^-)$ gives the expected value. Generally speaking, it is not assured that it converges, but in our case it is, since the $F$ are polynomials. b) $n$ is the initial number of variables and my $q$ is your $t$. Commented Apr 24, 2018 at 21:53